(untitled) (Andamios, Revista de Investigación Social, 2015)
In this paper, the television broadcasting of a union dispute in Argentina is analyzed using the theoretical framework developed by François Jost. The “Authenticating Promise” model is employed to identify the generic promise of television news shows. The model is tested by analyzing the television news sequences that communicated the underground workers’ emblematic union conflict in Buenos Aires City. The strategies and operations, employed by the television broadcasters that were used to fulfill their promise of showing the “objective truth” of this conflict, are also identified.